Napak Tilas as A Employing Heritage Walks for Local-History Learning and Character Education - Nur Aeni Marta; Humairah Nur Ramadilah Kurnia (Criksetra: Jurnal Pendidikan Sejarah, 2025)
This literature-based study evaluates the pedagogical effectiveness of napak tilas (direct visits to historical sites) as an integrative method for strengthening students’ local-history literacy and character education. Using a qualitative descriptive approach, the findings show that multisensory experiences at heritage sites enhance factual retention and historical empathy, whereas structured methodological guidance limits narrative distortion. When embedded in project-based learning and aligned with the five stages of historiography (topic selection, heuristics, source criticism, interpretation, and writing), napak tilas nurtures key values of nationalism, responsibility, and collaboration that correspond to the Indonesian “Profil Pelajar Pancasila”. The success of this method depends on equitable site access, supportive school policies, and teachers’ competence in source criticism. Schools are therefore encouraged to institutionalise napak tilas within the history curriculum, use virtual tours when physical visits are not feasible, and partner with museums as well as heritage communities to ensure scholarly validity and inclusivity.